2022
DOI: 10.1111/jocs.16942
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative Impella support on destination left ventricular assist device outcomes

Abstract: Background Although left ventricular assist device (LVAD) implantation is associated with improved heart failure survival, the impact of pre‐implantation Impella support on outcomes is unknown. We undertook this study to evaluate the impact of preoperative Impella support on LVAD outcomes. Methods We conducted a retrospective review of all Heartmate 3 LVAD implants. Primary stratification was by the need for preoperative Impella support with the 5.0/5.5 device. Longitudinal survival was assessed by the Kaplan–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Vascular access was predominantly via the axillary artery (98.6% among patients reported, of which 96.9% were right axillary among 386 patients reported), whereas direct aortic access represented a minority of patients (0.8%). Rates of concomitant ECMO with Impella support were 24.7% of 661 patients in studies 7 and Salas De Armas et al 16 report outcomes with Impella support only among patients surviving to device explant. These studies were excluded from qualitative synthesis of early survival after device implant.…”
Section: Treatment Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular access was predominantly via the axillary artery (98.6% among patients reported, of which 96.9% were right axillary among 386 patients reported), whereas direct aortic access represented a minority of patients (0.8%). Rates of concomitant ECMO with Impella support were 24.7% of 661 patients in studies 7 and Salas De Armas et al 16 report outcomes with Impella support only among patients surviving to device explant. These studies were excluded from qualitative synthesis of early survival after device implant.…”
Section: Treatment Characteristicsmentioning
confidence: 99%
“…In another analysis, Salas De Armas et al 16 reported 14 patients with cardiac cachexia bridged with Impella 5.5 or 5.0 to durable left ventricular assist device (LVAD). George et al 7 reported 84 patients successfully bridged to durable LVAD with or without temporary MCS using Impella 5.5. Ohira et al 13 reported seven patients who were treated with an "ECPELLA" strategy (ECMO + Impella 5.5).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer devices supply as much as 5.5 L of forward flow allowing for excellent circulatory support in critical heart failure patients, although data on their use as bridge to LVAD is limited. This retrospective study by George et al 1 reviewed all Heartmate 3 patients at a single institution requiring preoperative inotropes either with or without tMCS in the form of a surgical Impella 5.0/5.5. The investigators found similar survival at 30 days, 1, and 2 years post LVAD implantation with multivariable analysis demonstrating no difference in 1-or 2-year survival in the Impella group.…”
mentioning
confidence: 99%
“…This retrospective study by George et al 1 reviewed all Heartmate 3 patients at a single institution requiring preoperative inotropes either with or without tMCS in the form of a surgical Impella 5.0/5.5. The investigators found similar survival at 30 days, 1, and 2 years post LVAD implantation with multivariable analysis demonstrating no difference in 1‐ or 2‐year survival in the Impella group.…”
mentioning
confidence: 99%